Changes in vitamin D and matrix metalloproteinase-9 in submariners during a submerged patrol. Issue 2 (4th December 2013) - Baker, A; Wood, C L; Wood, A M; Timms, P; Allsopp, A J
Abstract : Objectives: To quantify changes in vitamin D and matrix metalloproteinase-9 (MMP9) in submariners over a single long patrol and compare the data to a group of non-deploying servicemen from their base port. Methods: A prospective time-series analysis was performed. Blood samples were taken from 49 submariners deploying on patrol and 43 shore-side controls from the base port (naval officers from base or non-deploying submariners), following a winter ashore at latitude 56° north. Samples were drawn immediately before the submarine sailed, in January, and again in the final week of patrol 85 days later. Paired pre-patrol and late samples from each individual were assayed together and changes in vitamin D and MMP9 were assessed. Results: Mean pre-patrol vitamin D concentrations were 58 and 49 nmol/L for the controls and submariners, respectively. Mean vitamin D concentrations increased in controls as expected (mean increase 12.6 nmol/L), but not in the submariners (mean decrease 1.6 nmol/L). MMP9 levels were significantly higher in submariners pre-patrol, and increased significantly during the patrol. There was a significant inverse correlation between MMP9 and vitamin D levels (r=−0.41, p=0.01). Conclusions: This is the first study to quantify vitamin D and MMP levels in submariners. Circulating vitamin D concentrations on board were insufficient to prevent a rise in MMP. This has potential for adverse health effects and requires further study.